Strategy to control magnetic coercivity by elucidating crystallization pathway-dependent microstructural evolution of magnetite mesocrystals - Bum Chul Park (Nature Portfolio, 2020)
Transient metastable intermediates play an important role in the crystallization process. Here, the authors unveil the microstructural changes in magnetite mesocrystals that depend on the intermediate polymorphism and the universal crystallite size effect on the magnetic coercivity of mesocrystals.